1986
DOI: 10.1172/jci112600
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of elastase in human emphysematous lungs.

Abstract: The current working hypothesis concerning the pathogenesis of humab pulmonary emphysema proposes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(64 citation statements)
references
References 36 publications
1
62
0
1
Order By: Relevance
“…It is noteworthy in this respect that HLE has been found in association with interstitial elastin in human emphysematous lungs [118]. These data suggest that elastinbound HLE retains catalytic activity in vivo, and may thereby contribute to the pathogenesis of pulmonary emphysema.…”
Section: Serine Proteinasesmentioning
confidence: 82%
“…It is noteworthy in this respect that HLE has been found in association with interstitial elastin in human emphysematous lungs [118]. These data suggest that elastinbound HLE retains catalytic activity in vivo, and may thereby contribute to the pathogenesis of pulmonary emphysema.…”
Section: Serine Proteinasesmentioning
confidence: 82%
“…The excessive activity of NE serves as a hallmark of the elastase/anti-elastase imbalance in the emphysematous lung (4,34,35,37). We describe in this article how NE, by releasing EGF-like and TGF-␣-like EGFR ligands, transactivates the EGFR/MEK/ERK cascade that signals to destabilize tropoelastin mRNA and thereby downregulates elastogenesis in a RFL-6 lung fibroblast cell culture model.…”
Section: Discussionmentioning
confidence: 98%
“…[7] It could be argued that the measurement of elastolytic activity in induced sputum may not accurately assess the activity in the interstitium, the site of extracellular matrix degradation in emphysema. However, the study which showed neutrophil elastase in close association with elastic fibers in the interstitium, in an amount that correlates with the severity of emphysema, [33] has been questioned in another study, that failed to reproduce these findings. [34] Furthermore, homogenates of lung removed in volume reduction surgery revealed significant elevations in MMP-9, with no significant increase in neutrophil elastase.…”
Section: Discussionmentioning
confidence: 97%